Correction: Stereodivergent synthesis of right- and left-handed iminoxylitol heterodimers and monomers. Study of their impact on β-glucocerebrosidase activity. Issue 37 (14th September 2017) - Stauffert, Fabien; Serra-Vinardell, Jenny; Gómez-Grau, Marta; Michelakakis, Helen; Mavridou, Irene; Grinberg, Daniel; Vilageliu, Lluïsa; Casas, Josefina; Bodlenner, Anne; Delgado, Antonio; Compain, Philippe
Abstract : Correction for 'Stereodivergent synthesis of right- and left-handed iminoxylitol heterodimers and monomers. Study of their impact on β-glucocerebrosidase activity' by Fabien Stauffert et al., Org. Biomol. Chem., 2017, 15, 3681–3705.